Representation Of Mathematics Expression Of Civil Engineering Students In Solving HOTS Problems - Hanida Emilia Dewi Pratiwi; Zukhrufurrohmah Zukhrufurrohmah; Dwi Priyo Utomo (Universitas Negeri Makassar, 2020)
The ability of students to represent mathematical expressions related to HOTS problems is still not good. This study aims to describe the representation of the mathematical expression of students in solving HOTS problems. This type of descriptive research using a qualitative approach in terms of aspects of the representation of mathematical expressions. The subjects of this study were 17 Civil Engineering students who were taking lectures in the academic year 2018/2019. The data collection technique in this research is the test item description. The instrument used was in the form of a test sheet. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing. The results showed that students could involve mathematical symbols correctly and appropriately in each stage of solving HOTS analysis type questions. Students can present other mathematical representations into mathematical expression representations and involve mathematical symbols correctly and appropriately in each stage of HOTS problem solving, both Evaluation type and Creating type. The ability of students to represent mathematical expressions related to HOTS problems is still not good. This study aims to describe the representation of the mathematical expression of students in solving HOTS problems. This type of descriptive research using a qualitative approach in terms of aspects of the representation of mathematical expressions. The subjects of this study were 17 Civil Engineering students who were taking lectures in the academic year 2018/2019. The data collection technique in this research is the test item description. The instrument used was in the form of a test sheet. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing. The results showed that students could involve mathematical symbols correctly and appropriately in each stage of solving HOTS analysis type questions. Students can present other mathematical representations into mathematical expression representations and involve mathematical symbols correctly and appropriately in each stage of HOTS problem solving, both Evaluation type and Creating type.